Microbial-Driven Butyrate Regulates Jejunal Homeostasis in Piglets During the Weaning Stage - Zhong, Xi; Zhang, Zhongwei; Wang, Shujin; Cao, Lili; Zhou, Lin; Sun, Aomin; Zhong, Zhendong; Nabben, Miranda (Frontiers in Microbiology, 2019)
Microbe-derived butyrate plays an important role in the gut health of young mammals during the weaning stage. A greater understanding of how butyrate regulates intestinal development is necessary for overcoming post-weaning diarrheal diseases. We aimed to investigate whether jejunal microbial metabolite butyrate modulates the apoptosis/proliferation balance and immune response in piglets during the post-weaning period of the first 3 weeks of life. On the one hand, during the first week post-weaning, the relative abundances of the dominant bacterial families Erysipelotrichaceae (P < 0.01) and Lachnospiraceae (P < 0.01) were increased, which induced decreases in both butyrate production (P < 0.05) and its receptor (G-protein coupled receptor 43) expression (P < 0.01). The resulting intestinal inflammation (inferred from increased TNF-α and IFN-γ expression) contributed to the onset of cell apoptosis and the inhibition of cell-proliferation along the crypt-villus axis, which were followed by impaired jejunal morphology (i.e., increased crypt depth) (P < 0.05) and intestinal dysfunction (i.e., decreased creatine kinase, and lactate dehydrogenase) (P < 0.05). On the other hand, during the second week post-weaning, the relative abundances of Lactobacillaceae (P < 0.01) and Ruminococcaceae (P < 0.05) were increased. The increases were accompanied by increased butyrate production (P < 0.05) and its receptor expression (P < 0.01), leading to the inhibition of cell apoptosis and the stimulation of cell proliferation via decreased pro-inflammatory cytokines and thereby the improvement of intestinal development and function. Herein, this study demonstrates that microbial-driven butyrate might be a key modulator in the maintenance of intestinal homeostasis after weaning. The findings suggest that strategies to promote butyrate production can maintain the apoptosis/proliferation balance via minimizing intestinal inflammation, and thereby improving post-weaning jejunal adaptation towards gut health.